Mesoporous single-crystal CoSn(OH)6 hollow structures with multilevel interiors - Wang, Zhiyu (2013)
Hollow nanostructures represent a unique class of functional nanomaterials with many applications. In this work, a one-pot and unusual ‘‘pumpkin-carving’’ protocol is demonstrated for engineering mesoporous single-crystal hollow structures with multilevel interiors. Single-crystal CoSn(OH)6 nanoboxes with uniform size and porous shell are synthesized by fast growth of CoSn(OH)6 nanocubes and kinetically-controlled etching in alkaline medium. Detailed investigation on reaction course suggests that the formation of a passivation layer of Co(III) species around the liquid-solid interface is critical for the unusual hollowing process. With reasonable understanding on the mechanism involved, this approach shows high versatility for the synthesis of CoSn(OH)6 hollow architectures with a higher order of interior complexity, such as yolk-shell particles and multishelled nanoboxes. The obtained CoSn(OH)6 hollow nanostructures can be easily converted to hollow nanostructures of tin-based ternary metal oxides with excellent photocatalytic and electrochemical properties.